Unraveling the Biochemical Strength of Gut Bacteria in Monopterus Cuchia - Mech, Banasri; Rahul Sarma; Jayshree Deka; Priyam Sarmah (Journal of Advanced Zoology, 2023)
The swamp eel, Monopterus cuchia, is a commercially important farmed fish in northeast India due to its medicinal and nutritional properties. The gut microbiota dysbiosis and homeostasis have been associated with the pathogenesis of swamp eel disease and food digestion. The gut microbiome in fish contributes to its growth and health by producing bio-compounds with nutritional functions. The objective of the present study was to find out the bioactivity of these gut bacteria with the help of various biochemical and morphological parameters. This study indicates that bacteria associated with M. cuchia have strong biochemical properties consistent with disease resistance. It requires further investigation of these bacteria up to the species level.